Pengaruh Komunikasi dan Motivasi Kerja Terhadap Kinerja Karyawan di Radisson Blu Bali Uluwatu - Ni Luh Erawati Widhi Astuti; Ni Wayan Sumetri; Muhammad Panji Mahardika (CV. ITTC INDONESIA, 2026)
The fundamental urgency of this research stems from the empirical detection of a decline in several key performance indicators (KPIs) in the frontline departments of Radisson Blu Bali Uluwatu, reflecting the importance of human resource governance in maintaining service excellence within the hyper-competitive hospitality industry. Tujuan Penelitian] This study aims to critically examine and measure the magnitude of the influence of organizational communication and work motivation on employee performance achievement in the operational environment of Radisson Blu Bali Uluwatu. Metode Penelitian] This research employs a quantitative approach with a causal-associative design. The population includes the entire workforce (152 people), with a sample of 61 individuals drawn through simple random sampling using the Slovin formula. Primary data were collected through a Likert-scale questionnaire and evaluated using multiple linear regression, partial t-test, simultaneous F-test, and the coefficient of determination via SPSS software. The analytical results validate that organizational communication has a positive and significant effect on employee performance (significance value 0.011 < 0.05). Work motivation also provides a positive and highly significant effect on performance metrics (significance value 0.000 < 0.05). The simultaneous evaluation proves that both variables jointly influence performance significantly with a contribution (R-square) of 71.9%, while the remaining 28.1% is explained by other variables outside the model. In conclusion, communication and work motivation are essential pillars for operational success, where work motivation emerges as the dominant determinant driving employee performance in a luxury resort ecosystem.